Factors influencing family takaful and life insurance demand - Norizan Remli
Despite progressive development in the last 15 years, the life insurance and family Takaful still, leave the huge potential for growth. Market penetration during this period was about 54 percent which is still far from the 75 percent of the Government target by 2020, of which this translates into a large protection gap among Malaysians. Given the above, the primary goal of this research is to investigate how this gap can be reduced by examining the external and internal factors that influence the demand for both family Takaful and life insurance in Malaysia. Interestingly, it was found that the market structure for the life insurance and family Takaful is different in which the life insurance was fragmented while family Takaful was dominant. It is important to investigate further the individual market structure as well as to make a comparison for the demand structure. Data from 2008-2016 was used to make a comparative analysis by way of general-least square over the panel data. The findings indicate that the demand for family Takaful is significantly influenced by firms size, agents' performance, gross domestic product, disposable income, and saving rate. While for the life insurance demand, the influencing factors are firms' income, firms' size, and agents' performance. The results of this study contribute to the industries by providing empirical evidence of the factors influencing the demand for family Takaful and life insurance in Malaysia. Also, this research could further provide a better understanding of the demand structure for the Takaful industry in Malaysia. Also, it could also benefit the regulators for appropriate policy refinement and the industry in improving market penetration and managerial activities to tap the huge market potential in Malaysia. For future research, the study should cover on the impact of legal system and government policies such as splitting of the license into general and family Takaful in which would benefit the family Takaful industry in the country.